2018
DOI: 10.1159/000486462
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-2 in Patients with Alopecia Areata: Relationship with Clinical Type and Duration of the Disease

Abstract: Background: Alopecia areata (AA) is a disease characterized by focally, nonscarring hair loss on the scalp or any hair-bearing surface. The etiology is unknown, although the evidence suggests that AA is an immunologically mediated disease. In the pathogenesis of AA, Th1 immune response is predominant. A special cytokine profile is created by Th1 cells, which disturbs the natural balance of the cytokine networks and leads to inflammatory reaction and follicle damage. Objective: The aim of our study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
(13 reference statements)
0
17
1
Order By: Relevance
“…IL-8 was significantly reduced (P < 0Á05) in AA (3Á37 pg mL À1 , 95% CI 3Á00-3Á75) compared with HCs (4Á28 pg mL À1 , 95% CI 3Á5-5Á0). Despite previous reports 14,39 we observed no change in levels of IFN-c between patients with AA and HCs, likely due to the high IFN-c expression observed in a small number of our HC samples. In addition, no change was observed in the levels of IL-15 or IL-12p40 between patients with AA and HCs.…”
Section: Circulating Levels Of Proinflammatory Cytokines Are Increasecontrasting
confidence: 99%
“…IL-8 was significantly reduced (P < 0Á05) in AA (3Á37 pg mL À1 , 95% CI 3Á00-3Á75) compared with HCs (4Á28 pg mL À1 , 95% CI 3Á5-5Á0). Despite previous reports 14,39 we observed no change in levels of IFN-c between patients with AA and HCs, likely due to the high IFN-c expression observed in a small number of our HC samples. In addition, no change was observed in the levels of IL-15 or IL-12p40 between patients with AA and HCs.…”
Section: Circulating Levels Of Proinflammatory Cytokines Are Increasecontrasting
confidence: 99%
“…IL-2 is a cytokine playing a role in immune memory with a proven relationship with autoimmune conditions, and the use of IL-2 or its receptors in immunotherapy is debatable. 14 Kasumagić-Halilovic et al 15 found higher IL-2 levels in AA patients as compared to that of the controls. No correlation was found between IL-2 levels and clinical type of AA or disease duration.…”
Section: Discussionmentioning
confidence: 96%
“…IgE recognizes exogenous antigens and signals through Fcɛ receptors (FcɛRs), including FcɛR I and FcɛR II, triggering an immunologic response. Moreover, it has been found that the levels of serum IgE significantly increase in patients with systemic lupus erythematosus, alopecia areata and other autoimmune disease [18,19].…”
Section: Discussionmentioning
confidence: 99%